Water Body Extraction from Multispectral Image Based on Spectral and Spatial Data - Jalwadi, Devashri (International Journal of Computer Sciences and Engineering, 2020)
Industrialization ,and urbanization lead to a change in land-use patterns and an increase in the utilization of water resources. In biogeochemical cycles, it requires good estimates of the areal extent and shape of water bodies. So timely monitoring of surface water and delivering data on the dynamics of surface water are essential for policy and decision-making processes. Change detection based on multispectral and multi-temporal remote sensing data is one of the most acceptable and ever-growing surface water change detection mechanisms in recent years. In this paper, a study has been conducted and we present an automated procedure that allows extraction of water body from a multispectral image based on its spectral data and spatial information.